2022
DOI: 10.3126/ejer.v4i1.44167
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Environment and Its Impact on Employee’s Performance in Nepalese Commercial Banks

Abstract: The purpose of the study is to examine the influence of workplace environment on employees’ performance of Nepalese commercial banks. A well-structured questionnaire was developed to collect data from 240 respondents using purposive sampling technique. Data analysis was done using Statistical Packages for the Social Sciences (SPSS) to generate mean, standard deviation, correlation, and regression analysis, and to diagnose the collected data. The results revealed that there is a significant influence of Job Aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Conversely, poor communication can engender negative consequences, impeding organizational performance and eroding employee morale (Anwar & Abdullah, 2021). As evidenced by prior research (Maharjan, 2021;Adhikari, 2020;Goet, 2022), the interplay between factors such as career development, organizational commitment, and communication significantly impacts organizational productivity and performance. Hence, it is imperative to delve deeper into these dynamics to elucidate their intricate relationships and implications within the Nepalese commercial banking context.…”
Section: Introductionmentioning
confidence: 97%
“…Conversely, poor communication can engender negative consequences, impeding organizational performance and eroding employee morale (Anwar & Abdullah, 2021). As evidenced by prior research (Maharjan, 2021;Adhikari, 2020;Goet, 2022), the interplay between factors such as career development, organizational commitment, and communication significantly impacts organizational productivity and performance. Hence, it is imperative to delve deeper into these dynamics to elucidate their intricate relationships and implications within the Nepalese commercial banking context.…”
Section: Introductionmentioning
confidence: 97%
“…The outcome of the study revealed that training leads to an increase in employee job satisfaction and training culture is very important for an organisation's development and success. Goet (2022) also conducted a study to observe the influence of workplace environment on employee's performance of Nepalese commercial banks. The independent variables used were job aids, team effort, physical environment and supervisor support and the dependent variable used were employee performance.…”
Section: Introduction and Study Objectivesmentioning
confidence: 99%
“…This is supported by data on employee turnover, which increases yearly. Several studies have proven that the work environment affects employee performance (Tleuken et al, 2022;Goet, 2022;Abun, 2022;Ibrahim et al, 2022;Ahakwa et al, 2021;Tasman et al, 2021;Badrianto & Ekhsan, 2020;Widyastuti et al, 2021;Na-Nan et al, 2019;Hafeez et al, 2019;Diamantidis & Chatzoglou, 2018;Hidayati et al, 2019;Solegar et al, 2018;Ikechukwu et al, 2019;Nzewi et al, 2017;and Siddiqi & Tangem, 2018). At the same time, several studies have shown that the work environment does not affect employee performance (Suparman Dadang, 2020; Riyadi, 2019;and Ahmad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%